Cerebral endothelial cell derived small extracellular vesicles improve cognitive function in aged diabetic rats - Zhang, Li; Li, Chao; Huang, Rui; Teng, Hua; Zhang, Yi; Zhou, Min; Liu, Xiangshuang; Fan, Baoyan; Luo, Hao; He, Annie; Zhao, Anna; Lu, Mei; et al. (Frontiers in Aging Neuroscience, 2022)
Small extracellular vesicles (sEVs) mediate cell-cell communication by transferring their cargo biological materials into recipient cells. Diabetes mellitus (DM) induces cerebral vascular dysfunction and neurogenesis impairment, which are associated with cognitive decline and an increased risk of developing dementia. Whether the sEVs are involved in DM-induced cerebral vascular disease, is unknown. Therefore, we studied sEVs derived from cerebral endothelial cells (CEC-sEVs) of aged DM rats (DM-CEC-sEVs) and found that DM-CEC-sEVs robustly inhibited neural stem cell (NSC) generation of new neuroblasts and damaged cerebral endothelial function. Treatment of aged DM-rats with CEC-sEVs derived from adult healthy normal rats (N-CEC-sEVs) ameliorated cognitive deficits and improved cerebral vascular function and enhanced neurogenesis. Intravenously administered N-CEC-sEVs crossed the blood brain barrier (BBB) and were internalized by NSCs in the neurogenic region, which were associated with augmentation of miR-1 and -146a and reduction of myeloid differentiation primary response gene 88 and thrombospondin 1 proteins. In addition, uptake of N-CEC-sEVs by the recipient cells was mediated by clathrin and caveolin dependent endocytosis signaling pathways. The present study provides ex vivo and in vivo evidence that DM-CEC-sEVs induce cerebral vascular dysfunction and neurogenesis impairment and that N-CEC-sEVs have a therapeutic effect on improvement of cognitive function by ameliorating dysfunction of cerebral vessels and increasing neurogenesis in aged DM rats, respectively.